2016
DOI: 10.2147/ndt.s113220
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and coping in military cadre candidates

Abstract: BackgroundSoldiers must cope with stressors during both military operations and training if they are to accomplish their missions successfully and stay mentally stable. This holds true particularly for military superiors, as they bear greater responsibilities and must meet greater demands during both deployment and training. Accordingly, in the present study, we investigated whether recruits chosen for further promotion at the end of basic training differed with regard to psychological distress and coping stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Given this general background and shifting to the military context, military personnel are exposed to different kinds of stress [ 18 , 19 ]. Almost by definition, people in the military are executing dangerous and stressful work and accordingly, they also have an elevated risk of suffering from stress-related disorders following military deployment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this general background and shifting to the military context, military personnel are exposed to different kinds of stress [ 18 , 19 ]. Almost by definition, people in the military are executing dangerous and stressful work and accordingly, they also have an elevated risk of suffering from stress-related disorders following military deployment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given this general background and shifting to the military context, military personnel are exposed to different kinds of stress [ 18 , 19 ]. Almost by definition, people in the military are executing dangerous and stressful work and accordingly, they also have an elevated risk of suffering from stress-related disorders following military deployment [ 18 ]. Not surprisingly, and compared to those not in the military, military personnel are at a higher risk of developing other psychological disorders such as depression, anxiety, and alcohol abuse [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People have different coping abilities to deal with demands and experiences, which may be deemed to be more stressful to some. For instance, deadlines, workrelated pressure (such as upholding good service) and complex problem solving can cause higher levels of anxiety and stress amongst individuals (Brand, Nakkas, & Annen, 2016). Overall, the literature indictates that mental health issues can contribute negatively in several ways throughout the lifespan, and public health incentives are a long way from influencing the current way mental health is identified and treated (see Mantzios, 2020;Mantzios, Egan, & Cook, 2019a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The use of a perceived stress and coping strategies measurement combination is increasingly common in studies of law enforcement officers [3, 23, 24, et al]. It was shown that the use of productive coping strategies is associated with a lower severity of PTSD signs [25], enhancing performance and cognitive function [26] and the development of life skills [27], a decrease in psychological distress [28] and social anxiety [29]. However, this influence is largely determined by factors of the so-called "adaptogenic" context [30], i.e.…”
Section: Introductionmentioning
confidence: 99%